Alteration of the Optoelectronic Properties of CuInS2 Quantum Dots via Colloidal Annealing - Dehm, Katharina; Zanetti, Alberto; Fett, Bastian; Mauritz, Vincent; Hamburger, Robert C.; Langford, Daniel; Guldi, Dirk Michael; Young, Elizabeth R.; Mandel, Karl; Crisp, Ryan (Crystal Growth and Design, 2024)
Colloidal semiconductor quantum dots (QDs) have tunable optoelectronic properties, thereby making them interesting materials for applications involving light-matter interactions. However, crystallographic and surface defects greatly impair their potential performance in devices. Herein, we present a straightforward approach to improve the quality of copper indium disulfide (CuInS2) QDs by adjusting the parameters of the colloidal synthesis. By the introduction of prolonged heating times after the nanocrystal growth has already gone to completion, defect states are partially removed. This “colloidal annealing” for varying time spans (from 5 up to 90 min) with longer annealing times correlating with a decreased ratio of emission from defect states compared to band edge emission, results in enhanced color purity. At shorter annealing times, the defects removed are mainly structural, indicated by the transition from mixed crystal phases to an almost phase-pure material. At longer annealing times, further improvements are linked to surface defect removal. Findings from transient absorption spectroscopy further confirm this trend by revealing a decrease in the intensity of a photoinduced absorption feature associated with sub-band gap states compared to the band edge bleach signal. These findings highlight the applicability of colloidal annealing as a straightforward strategy for direct material optimization during colloidal synthesis.<br

Tartaric acid-derived chiral carbon nanodots for catalytic enantioselective ring-opening reactions of styrene oxide - Zhao, Xinyi; Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Zhang, Zhipeng; Liu, Qi; Drewello, Thomas; Guldi, Dirk Michael; Chen, Xiaoqing (Chemical Communications, 2024)
Chiral carbon nanodots (CNDs) were fabricated through the hydrothermal processing of sulfanilic acid and chiral tartaric acid, exhibiting outstanding catalytic performance for the chiral catalysis of the ring-opening reaction. Furthermore, the catalytic mechanism was proposed to understand the link between the chiral structure and the performance of the catalyst.
CRIS-Team Scopus Importer:2024-09-27

Understanding the Visible Absorption of Electron Accepting and Donating CNDs - Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Bo, Yifan; Schol, Peter; Scharl, Tobias; Zhao, Xinyi; Crisp, Ryan; Drewello, Thomas; Clark, Timothy; Cadranel, Alejandro; et al. (Small, 2023)
Carbon nanodots (CNDs) synthesized from citric acid and formyl derivatives, that is, formamide, urea, or N-methylformamide, stand out through their broad-range visible-light absorbance and extraordinary photostability. Despite their potential, their use has thus far been limited to imaging research. This work has now investigated the link between CNDs’ photochemical properties and their chemical structure. Electron-rich, yellow carbon nanodots (yCNDs) are obtained with in situ addition of NaOH during the synthesis, whereas otherwise electron-poor, red carbon nanodots (rCNDs) are obtained. These properties originate from the reduced and oxidized dimer of citrazinic acid within the matrix of yCNDs and rCNDs, respectively. Remarkably, yCNDs deposited on TiO2 give a 30% higher photocurrent density of 0.7 mA cm−2 at +0.3 V versus Ag/AgCl under Xe-lamp irradiation (450 nm long-pass filter, 100 mW cm−2) than rCNDs. The difference in overall photoelectric performance is due to fundamentally different charge-transfer mechanisms. These depend on either the electron-accepting or the electron-donating nature of the CNDs, as is evident from photoelectrochemical tests with TiO2 and NiO and time-resolved spectroscopic measurements.
Created from Fastlane, Scopus look-up
Keywords: carbon nanodots; excited state; photoelectrochemistry; semiconductors; time-resolved spectroscopy